Hubungan Karakteristik, Aktivitas Seks, Kontrasepsi, Vaginal Douching dengan Infeksi Menular Seksual Pada Pekerja Seks Komersial Di PSKW Mulya Jaya Pasar Rebo Jakarta Tahun 2011 - Royani Chairiyah; Warsiningsih Warsiningsih (Jurnal Persada Husada Indonesia, 2015)
In Indonesia, sexually transmitted infections are most commonly found were syphilis and gonorrhea.The prevalence of sexually transmitted infections is very high in Indonesia was found in 4 cities Bandung,Surabaya, Jakarta and Medan. Increase in disease is evident since the year 2003 increased 15,4% while in 2004continued to increase to 18,9%, while in 2005 increased to 22,1%. The trend in increased spread of disease iscaused by the sexual behavior of multiple partners, a sexual relationship outside marriage and outside marriageare high enough.Objectives to knowing the relationship between characteristics, sexual activity, vaginaldoching, contraception on the incidence of STIs in sex workers in Pasar Rebo PSKW Mulya Jaya Jakarta in2011.The surveys design used, descriptive and cross sectional study design in 52 sex workers. Data analysis withchi-square and multiple logistic regression.Results the variables that have a meaningful relationship with IMSdisease are age (P value = 0,036), education (P value = 0,025) and contraceptive use (P value =0,043).Conclusion out of 17 female sex workers are exposed to sex transmitted disease almost all of syphilis, gonorrheaand chlamydia. The variables age, education and contraceptive use relate to incidence of sexually transmittedinfection in female sex workers.Suggestion is expected in the future will go on the subjects of social interaction,group development, social support and counseling by method of field studies of various groups in society tolearning for students.Keywords: Female sex workers and Incidence Sex Transmitted Infections.